2001
DOI: 10.1046/j.1365-2141.2001.03127.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage glycosylphosphatidylinositol anchor‐deficient haematopoiesis in untreated aplastic anaemia

Abstract: Summary. Aplastic anaemia and paroxysmal nocturnal haemoglobinuria (PNH) are closely related disorders. In PNH, haematopoietic stem cells that harbour PIGA mutations give rise to blood elements that are unable to synthesize glycosylphosphatidylinositol (GPI) anchors. Because the GPI anchor is the receptor for the channelforming protein aerolysin, PNH cells do not bind the toxin and are unaffected by concentrations that lyse normal cells. Exploiting these biological differences, we have developed two novel aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 56 publications
(83 reference statements)
4
56
0
1
Order By: Relevance
“…The presence of PNH clones in 25% of patients diagnosed as AA is in line with literature data, which describe the frequency of PNH cells in 22% to 68% of AA patients (5,8,9,12,19,20,25) . This prevalence variability occurs due to methodological differences between the used tests, which define different limits of analytical sensitivity.…”
Section: The Black Bar Represents the Cut-off Point (01%) Chosen Forsupporting
confidence: 76%
“…The presence of PNH clones in 25% of patients diagnosed as AA is in line with literature data, which describe the frequency of PNH cells in 22% to 68% of AA patients (5,8,9,12,19,20,25) . This prevalence variability occurs due to methodological differences between the used tests, which define different limits of analytical sensitivity.…”
Section: The Black Bar Represents the Cut-off Point (01%) Chosen Forsupporting
confidence: 76%
“…[1][2][3][4][5][6] We previously demonstrated that a minor (less than 1%) population of CD55 Ϫ CD59 Ϫ granulocytes could be detected in the peripheral blood of patients with AA at a much higher frequency than previously reported. 7 Given that the proportion of PNH-type granulocytes decreased in most patients in association with hematologic recovery after successful immunosuppressive therapy, such PNH-type cells appeared to be derived from PNH-type progenitor cells that evaded immune system attack against hematopoietic progenitor cells.…”
Section: Introductionmentioning
confidence: 79%
“…11 Interestingly, small populations of PNH-like granulocytes can be found in up to 50% of patients with MDS (usually 0.01-5% PNH granulocytes) 12 and AA (usually 0.1-10% PNH granulocytes). 13,14 PIG-A mutant blood cells (~0.002%) can also been found in healthy control subjects. 15,16 In contrast to PNH, most PIG-A mutations in healthy controls are transient and arise from colony forming cells that have no self-renewal capacity and no ability to differentiate into T lymphocytes.…”
Section: Introductionmentioning
confidence: 96%